BS EN IEC 60966-2-8. Radio frequency and coaxial cable assemblies. Part 2-8. Detail specification for cable assemblies for radio and TV receivers. Frequency range up to 3000MHz, Screening class A++, IEC61169-47 connectors (15th November 2019) - British Standards Institution,
No abstract available